A prognostic classification system for extent of resection in IDH-mutant grade 2 glioma: A report by the RANO resect group. - Karschnia, Philipp; Young, Jacob S.; Wijnenga, Maarten; Wagner, Arthur; Schnell, Oliver; Häni, Levin; Esquenazi, Yoshua; Vik-Mo, Einar; Rudà, Roberta; Vogelbaum, Michael A.; Hervey-Jumper, Shawn L.; Beck, Juergen; et al. (Journal of Clinical Oncology, 2025)
Background: The effects of resection in IDH-mutant grade 2 gliomas remain controversial since terminology for extent of resection was inconsistently applied across trials. We aimed to (I) establish a standardized classification system for extent of resection and (II) assess the impact of supramaximal resection on survival in IDH-mutant astrocytomas and 1p19q-codeleted oligodendrogliomas. Methods: Patients with newly diagnosed grade 2 IDH-mutant glioma meeting the WHO 2021 criteria were identified across sixteen centers in the USA, Europe, and Asia as part of the RANO resect effort. Additional patients from UCSF served for validation. Kaplan-Meier analyses and log-rank tests were applied to calculate survival, and Cox’s proportional hazard regression model to adjust for multiple variables (significance level: p ≤ 0.05). Results: We identified 1391 newly diagnosed IDH-mutant gliomas grade 2 between 1993-2024, of which 728 patients (379 astrocytoma, 349 oligodendroglioma) received no adjuvant treatment and allowed to study the effects of resection. Smaller post-operative T2/FLAIR tumor remnants were favorably associated with outcome. We classified those patients according to residual T2/FLAIR tumor volumes: patients with ‘maximal T2/FLAIR resection’ (class 2; 0-5 cm3 remnant) had superior progression-free and overall survival compared to ‘submaximal T2/FLAIR resection’ (class 3; 5-25 cm3 remnant) or ‘minimal T2/FLAIR resection’ (class 4; >25 cm3 remnant), with 10-year survival rates of 82.2% vs. 75.0% vs. 45.6% (respectively; p = 0.001). Resection of non-infiltrated structures beyond T2/FLAIR borders provided an additional survival benefit as characterized by a 10-year survival rate of 97.5%; thus defining class 1 ‘supramaximal T2/FLAIR resection’ (HR for OS vs. class 2: 0.24, CI 0.1-0.5 / in astrocytoma: 0.26, CI 0.1-0.7 / in oligodendroglioma: 0.21, CI 0.1-0.9). Effects of extensive resection on survival unfolded after 3 years in astrocytomas, whereas survival curves separated after 6-8 years in oligodendrogliomas. The prognostic relevance of the four-tier classification was conserved in a multivariate analysis controlling for clinical markers including pre-operative tumor and 1p19q-codeletion, in subgroups of either astrocytomas or oligodendrogliomas, and in a separate cohort of 586 patients who received adjuvant chemo-/radiotherapy. The prognostic value of the classification was further validated in the external UCSF cohort of 381 grade 2 IDH-mutant gliomas (p = 0.001). Conclusions: The proposed ‘RANO classification for extent of resection’ serves as prognostic tool for patient stratification in grade 2 IDH-mutant gliomas. While effects of extensive surgery are evident earlier in astrocytomas, ‘supramaximal’ resection translates into a survival benefit for both astrocytomas and oligodendrogliomas and should be characterized in clinical trials.
CRIS-Team Scopus Importer:2025-12-19